Analisis Ekonomi Kelembagaan Keuangan Masyarakat: Studi Modal Sosial Dan Dinamika Pendapatan Dalam Prespektif Ekonomi Syariah - Fauzi Arif Lubis (Universitas Islam Negeri Sumatera Utara, 2023)
Institutional economic analysis is one of the important studies in modern economics, especially in assessing the relationship of social capital and income dynamics as a construct variable in the perspective of Islamic economics. The study uses a systematic literature review approach originating from accredited journals, the data reduction process is carried out by structuring exogenous research topics in mapping literature that is closely related to the problem unit. The results of the study provide information that networks, norms, trust, reciprocity are the identified factors that are dominant in constructing social capital factors and income dynamics towards institutional economics, especially in the Islamic economic perspective, the aspect of shared value is the dominant factor which is known to originate from public trust in religious values. from sharia-compliant financial institutions. Another finding is that most of the research is dominated by institutional economic perspectives, social capital and income dynamics are interrelated and influence each other and this also happens within the Islamic economic framework. Strong and quality social capital can affect the dynamics of income in society, which is agreed by most of the previous research has a significant positive impact on economic development.